The impact of Islam on post-independence Malaysian society and rule: challenges and prospects - Akhmetova, Elmira; Ahmad, Nadzrah (2018)
This paper discusses the relationship between the state, civil society and the country’s dominant religion, Islam, in Post-Independence Malaysia since 1957.